CALCULATION OF STATIC PARAMETERS OF SILICON DIODE CONTAINING δ-LAYER OF TRIPLE-CHARGED POINT DEFECTS IN SYMMETRIC p–n-JUNCTION - N. A. Poklonski; A. I. Kovalev; N. I. Gorbachuk; S. V. Shpakovski (Приборы и методы измерений)
The study of semiconductor materials and devices containing a narrow layer of impurity atoms and/or intrinsic point defects of the crystal lattice is of fundamental and practical interest. The aim of the study is to calculate the electric parameters of a symmetric silicon diode, in the flat p–n-junction of which a δ-layer of point triple-charged t-defects is formed. Such a diode is called p–t–n-diode, similarly to p–i–n-diode.Each t-defect can be in one of the three charge states (−1, 0, and +1; in the units of the elementary charge). It is assumed that at room temperature all hydrogen-like acceptors in p-region and hydrogen-like donors in n-region are ionized. It was assumed that the cross-section for v-band hole capture on t-defects is greater than the cross-section for c-band electron capture on t-defects.The system of stationary nonlinear differential equations, which describe in the drift-diffusion approximation a migration of electrons and holes in semiconductors, is solved numerically. The static capacityvoltage and current-voltage characteristics of the silicon diode with nondegenerate regions of pand n-type of electrical conductivity are calculated for forward and reverse electric bias voltage.It is shown by calculation that in the p–t–n-diode containing the δ-layer of t-defects, at the forward bias a region of current density stabilization occurs. At the reverse bias the current density in such a diode is much greater than the one in a p–n-diode without t-defects. With the reverse bias the capacitance of the p–t–n-diode, in contrast to the p–n-diode, increases at first and then decreases.